Interactive Media Learning by Using Powtoon Application to Improve Learning Comprehension Lightly Independent Students - Wanty Khaira; Mulia (Program Studi Pendidikan Profesi Guru Fakultas Tarbiyah dan Keguruan UIN Ar-Raniry Banda Aceh, 2023)
Media is a tool to delivery messages and can stimulate the thoughts, feelings, and willingness of the audience (students) so that it can encourage them to study. The use of media creatively enables students to learn better and to develop understanding of learning. In the world of education, the success of students in the teaching and learning process is greatly influenced by the media used by the teacher. In this case, interactive media with the Powtoon application is an alternative for teachers in the teaching and learning process, especially in the learning process for students with mild mental retardation. The purpose of this study was to find out whether interactive media learning with the powtoon application could improve students' understanding of mild mental retardation. This class action research had 4 mild mentally retarded students as research subjects. The individual KKM that has been set is 75 and for learning completeness is 80%. Data collection techniques were carried out through observation and tests. From the results of teacher activities in cycle I and cycle II, the increase in student understanding results can be seen from the analysis of student tests in the implementation of cycle I learning before using interactive learning media, namely obtaining a score of 52.5% in the